1996
DOI: 10.1139/v96-126
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical valence indices from the one-determinantal difference approach

Abstract: The recently introduced quadratic (two-electron) valence indices, ionic and covalent, derived from the HartreeFock finite-difference approach, are applied to selected organic and inorganic molecules to demonstrate their utility in monitoring chemical bonding patterns in molecular systems. The indices are defined in terms of differerences between simultaneous probabilities of finding two electrons on specified atoms, calculated from the molecular and separated-atomlimit (SAL) wave functions, respectively, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(93 citation statements)
references
References 25 publications
3
90
0
Order By: Relevance
“…The NOCV have been derived from the NalewajskiMrozek valence theory [40][41][42][43][44][45] as eigenvectors that diagonalize the deformation density matrix. It was shown that the pairs of the natural orbitals for chemical valence (w -k , w k , corresponding to eigenvalues -v k and v k ) decompose the differential density Dq into NOCV-contributions (Dq k ):…”
Section: Computational Details and Modelsmentioning
confidence: 99%
“…The NOCV have been derived from the NalewajskiMrozek valence theory [40][41][42][43][44][45] as eigenvectors that diagonalize the deformation density matrix. It was shown that the pairs of the natural orbitals for chemical valence (w -k , w k , corresponding to eigenvalues -v k and v k ) decompose the differential density Dq into NOCV-contributions (Dq k ):…”
Section: Computational Details and Modelsmentioning
confidence: 99%
“…A similar description follows [1][2][3] from the Wiberg-type bond-multiplicities formulated in the MO theory [4,[14][15][16][17][18][19][20][21][22][23]. In MO description the chemical interaction between, say, two (valence) AO or general basis functions originating from different atoms is strongly influenced by their direct overlap and interaction, which both condition the bonding effect experienced by electrons occupying their bonding combination in the molecule, compared to the non-bonding reference of electrons on separated AO.…”
Section: R F Nalewajski (B)mentioning
confidence: 99%
“…This quadratic bond-multiplicity concept has been subsequently extended [14][15][16] and generalized in terms of the bond-orders from the two-electron difference approach [17][18][19][20][21][22][23]. It follows from Eq.…”
Section: Indirect Conditional Probabilitiesmentioning
confidence: 99%
“…It vanishes for the lone-pair configurations, when P = (0 or 1), This simple model thus properly accounts for the competition between the bond covalency and ionicity, while preserving the single bond-order measure reflected by the conserved single IT multiplicity of the chemical bond. Similar effects transpire from the quadratic bond indices formulated in the MO theory [87][88][89][90][91][92][93][94][95][96][97]. For example, the plot of Wiberg bond-order [87] for this model (see Fig.…”
Section: Illustrative Example: Two-orbital Model Of Chemical Bondmentioning
confidence: 62%